EQUIPPING TEACHERS WITH 21ST CENTURY SKILLS: TRAINING ON WEBSITE AND ICT-BASED LEARNING MEDIA CREATION - Ahmar, Dewi Satria; Rahmawati, Sitti; Ahmar, Ansari Saleh; Azzajjad, Muhammad Fath; Wahab, Zamil; Tonio, Sarinah Emilia; Muliani, Sri (LPPM Univ. Ibn Khaldun Bogor, 2024)
Teachers in the twenty-first century need to be digitally literate in order to raise the calibre of instruction. According to a scenario analysis conducted at SMAN 1 Sindue Tobata, over 80% of instructors require training in the development of ICT and website-based learning materials since doing so lowers student involvement and the quality of instruction. Teachers were given extensive training to enable them to build and utilise digital learning resources in order to solve this problem. Because of this, over 90% of the trainees were able to develop online and ICT platforms to provide engaging and useful learning materials. As a result, this training not only helps instructors meet their skill demands, but it also greatly enhances the teaching and learning process in the digital age. For the training programme to continue supporting teachers' professional growth in the future, sustainability is crucial. This project, financed by the Directorate of Research, Technology and Community Service (DRTPM), with contract number Manual.164/E5/DT.05.00.2024, is to assist in the enhancement of the quality of instruction.